Rural Roads, Poverty, and Resilience : Evidence from Ethiopia - Nakamura, Shohei; Bundervoet, Tom; Nuru, Mohammed (Taylor and Francis, 2021)
This study analyses the linkage between the recent rural road development and household welfare, resilience, and economic conditions in Ethiopia. The empirical approach relies on a difference-in-differences matching method, taking advantage of a nationally representative household survey and an original road database, both of which are panel data spanning the period 2012–2016. The results of the econometric analysis suggest that Ethiopia’s rural road development was associated with a significant increase in household welfare or significant smaller losses in household consumption during the severe droughts. In addition, rural roads in very remote areas were associated with farmers’ sales of a larger share of their harvests and higher chance of fertiliser use. Rural road development was also associated with a higher likelihood of earning income from wage employment, particularly for women and youth. Taken together, the results suggest that, by connecting remote communities to markets and the main road network, rural roads have substantially supported the welfare and resilience of rural households in shock-prone Ethiopia.